Penguatan Pemahaman Ekualisasi Pajak melalui Program Smart Tax Smart Talent di Era Digital - Ari Sarah Sofura; Yulia Khoerunisa; Eka Yulianto; Dian Novitasari; Safira Nur Alifa; Salsabila Salwa Insyirah (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
Tax is a mandatory contribution to the state owed by individuals or entities, which is mandatory under the law, without receiving any direct compensation and is used for state purposes for the greatest prosperity of the people. (KUP Law). The Taxation System (Coretax), which became operational in 2025, with all its news aspects, has attracted much public attention, especially from businesses and individuals, regarding developments in tax reporting, procedures, and regulations in Indonesia. The public is required to understand tax equalization and related aspects, as it can impact the sustainability of both businesses and individuals. The webinar